Resolution of scale issues in an integrated catchment information system for the rivers of the Kruger National Park - Jewitt, G. P. W.(Graham Paul Wyndham) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, 1998.